2022
DOI: 10.1017/jfm.2021.1067
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal miscible displacements through porous media: the interplay between viscous fingering and gravity segregation

Abstract: We consider miscible displacements in two-dimensional homogeneous porous media where the displacing fluid is less viscous and has a different density than the displaced fluid. We find that the dynamics evolve through nine possible regimes depending on the viscosity ratio, strength of density variations and the strength of the background flow, as characterized by the Péclet number. At early times the interface is dominated by longitudinal diffusion before undergoing a transition to a slumping regime where verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Axisymmetric perturbations decay faster than θ-dependent perturbations, with the error decaying proportional to T −1 as has been found previously for unconfined gravity currents (Grundy & McLaughlin 1982;Mathunjwa & Hogg 2006). For a different stability argument in the case of axisymmetric perturbations, see the Appendix of Nordbotten & Celia (2006).…”
Section: Linear Stability For Small Density Difference (G 1)supporting
confidence: 59%
See 4 more Smart Citations
“…Axisymmetric perturbations decay faster than θ-dependent perturbations, with the error decaying proportional to T −1 as has been found previously for unconfined gravity currents (Grundy & McLaughlin 1982;Mathunjwa & Hogg 2006). For a different stability argument in the case of axisymmetric perturbations, see the Appendix of Nordbotten & Celia (2006).…”
Section: Linear Stability For Small Density Difference (G 1)supporting
confidence: 59%
“…At later times, it is generally assumed that the fluids segregate vertically due to buoyancy, and a stable interface between the input and ambient fluids develops, which seems to be corroborated by laboratory experiments (Nordbotten & Celia 2006;Pegler, Huppert & Neufeld 2014;Guo et al 2016). It has also been shown that the combination of buoyancy and mixing between the fluids can suppress the Saffman-Taylor instability at long times (Tchelepi 1994;Riaz & Meiburg 2003;Nijjer, Hewitt & Neufeld 2022). However, for sharp-interface gravity currents in confined porous media, stability of the gravity current solution has not yet been confirmed and the flow physics that suppresses viscous fingering is not fully understood.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations